Pendampingan Sertifikasi Produk Halal bagi Pelaku Usaha Mikro dan Kecil di Desa Tanjung - Deykha Aguilika; Muh. Syarif; Muhammad Ersya Faraby; Yudha Dwi Putra Negara (Keris: Journal of Community Engagement, 2024)
The number of MSMEs in Pamekasan Regency itself has increased from 2015-2020, in 2020 the number of MSMEs in Pamekasan Regency reached 9,441 MSMEs. The percentage of fostered MSMEs shows a fluctuating number from 2015-2020, in 2020 the percentage of fostered MSMEs in Pamekasan Regency reached 62.67%. The percentage of MSMEs that received capital assistance in Pamekasan Regency has increased from 2015-2020, in 2020 the percentage of MSMEs that received capital assistance in Pamekasan Regency reached 88%.To increase economic empowerment, the Abdimas team in collaboration with the Halal Center of Trunojoyo Madura University and students will hold training activities and assistance in registering halal certificates to support the marketability and commerciality of products produced by micro and small entrepreneurs in Tanjung Village, Pademawu District, Pamekasan Regency. The focus of this activity aims to: (1) Human resource development (2). Increase awareness of halal products and halal certification (3). Introducing digitalization of procedures and procedures for applying for a halal certificate to BPJP through SiHalal (4). Assisting in applying for halal certification to Bpjph (5) Verification and validation through the SiHalal system. Abdimas targets are micro and small businesses in the scope of food and beverages in Tanjung Village, Pademawu District, Pamekasan Regency. Activities are divided into 3 (three) stages, namely preparation, implementation, and evaluation.